Ownership and Spatial Distribution of Eagle Ford Mineral Wealth in Live Oak County, Texas. Issue 4 (2nd October 2017) - Murphy, Trey; Brannstrom, Christian; Fry, Matthew
Abstract : U.S. unconventional hydrocarbon production is a driver of economic growth, but mineral wealth ownership is poorly understood and shrouded in "local wealth" mythology that claims royalties from hydrocarbons mostly benefit people who live near sites of production. Mineral property tax appraisals, as proxies for mineral wealth from Live Oak County, a representative Eagle Ford Shale county in Texas, show that 96 percent of assessed mineral wealth concentrates among energy firms and individuals in Texas metropolitan regions; 1.95 percent of mineral wealth remains "local" to the production county, challenging local wealth myths. Deviating from nation-state scalar approaches, local and regional spatial studies of other energy regions might reveal similar wealth distributions, enabling generalizations about hydrocarbon production economic outcomes.